2018
DOI: 10.3390/w10070903
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Hydrogeochemical Processes on Karst Groundwater Using a Mass Balance Model in the Liulin Spring Area, North China

Abstract: Abstract:Exploring the hydrogeochemical processes of karst groundwater has significant meaning for protecting local groundwater systems in semi-arid areas. Taking a typical semi-arid karst groundwater system-the Liulin spring area-as the research region, hydrogeochemical processes from rainfall infiltration to formation of higher total dissolved solids (TDS) water were studied, applying a mass balance model and the prediction of water chemical components in the focus area was explored. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…It has been shown that land use and anthropogenic effects are factors that likely lead to the variability in water chemistry of the underground water resources within karst semi-arid areas. Same conclusion was highlighted in paper [13] for the case study of the karst arid areas in Northern China.…”
Section: Introductionsupporting
confidence: 67%
“…It has been shown that land use and anthropogenic effects are factors that likely lead to the variability in water chemistry of the underground water resources within karst semi-arid areas. Same conclusion was highlighted in paper [13] for the case study of the karst arid areas in Northern China.…”
Section: Introductionsupporting
confidence: 67%
“…Karst aquifers crop out in approximately 12% of the global land surface and offer water resource for almost 25% of the world population [1][2][3][4]. In the past several decades, karst systems have been widely studied in aspects of the conceptual model [5][6][7], recharge sources [8][9][10], flow types [11,12], hydrogeochemical processes [13][14][15][16][17][18][19][20][21], hydrodynamics [22][23][24], responses to climate changes [25][26][27], and numerical modeling [28][29][30]. However, the heterogeneity and anisotropy of karst conduits and fractures created by uneven groundwater flow give rise to the complex hydrogeological conditions and make it difficult to understand and characterize the karst system [4,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 9 shows the paleocave geobody engraving results for the runoff zone. The 3D visualization structure shows that the current wells encountered the sinkhole and the main channel [67], and the next drilling considered multiple horizontal wells and high-angle wells to effectively increase the length of the wells in the paleokarst reservoir. For example, drilling a horizontal well along the top of a main channel between TK405 and T403 could effectively increase the hydrocarbon production.…”
Section: Three-dimensional Structure Of Paleokarst Systemmentioning
confidence: 99%